Clinical effectiveness of training for awareness, resilience, and action for adolescents and young adults with depression: The pilot phase of a multicenter randomized controlled trial - Ekbäck, Erik; Rådmark, Lina; Granåsen, Gabriel; Svärling, Rachel; Sörlin, Matilda; Schönbeck, Caspar; Henje, Eva (Frontiers in Psychiatry, 2023)
Abstract Depression is a top-ranking global health concern increasing in magnitude. Available treatments for adolescents and young adults are not convincingly effective and relapse rates remain high. Training for Awareness, Resilience and Action (TARA) is a group treatment program targeting specific pathophysiological mechanisms of depression in young people. TARA is feasible, acceptable, preliminarily efficacious in depressed American adolescents, and it affects postulated brain-circuitry. As an initial step of a multicenter randomized controlled trial (RCT) we performed a single-arm multicenter pilot-study on TARA. Thirty-five depressed individuals (15-21 years old, 28 females) received TARA for 12 weeks face-to-face or online. Data was collected before (T0), during, and after the intervention (T1). The trial was pre-registered at clinicaltrials.gov, NCT Registration: identifier [NCT04747340]. Feasibility outcomes included recruitment, attendance rates, and session ratings. Adverse events were recorded weekly and extracted from medical records at the end of the trial. Primary effectiveness outcome was self-rated depression severity on Reynolds Adolescent Depression scale 2nd ed. at T1. Secondary outcomes were Children’s Depression Rating Scale-revised (CDRS-R) and Multidimensional Anxiety Scale for Children (MASC) at T1. TARA was feasible and safe in the present trial. No significant RADS-2-change was seen (adjusted mean difference -3.26, 95 % CI –8.35 to 1.83; p=0.20), however a significant decrease in CDRS-R scores is reported (adjusted mean difference -9.99, 95 % CI –14.76 to -5.22; p<0.001). MASC-scores did not change significantly (adjusted mean difference 1.98, 95 % CI –0.96 to 4.91; p=0.18). Additional feasibility aspects are presented and discussed. Limitations include substantial loss-to-follow-up, no randomization to control, and that some participants received concomitant treatment(s). The Coronavirus pandemic complicated both implementation and interpretation of the trial. In conclusion TARA was feasible and safe in depressed adolescents and young adults. Preliminary signs of effectiveness were seen. The initiated RCT will be important and worthwhile to conduct, and several improvements to the design are suggested based on the present results.